The Application of Fusion Learning Model Talking Stick and Course Review Horey To Increase Activeness and Learning Outcomes - Hartanti, Desi Ayu; Hardinto, Prih (Unversitas Negeri Malang, 2017)
During learning process in school, there are many factors which relate one another. They determine how well learning process can be achieved. That factors are teachers, students, curriculum, lesson, test, and environment. The purpose of this study is to solve a problem at students grade X 2 MA Miftahul Falah Pasuruan, these problems are activeness and learning outcomes with the implementation of learning model Talking Stick and Course Review Horey. This study had been done in two cycles where every cycle has 3 times meetings. Data obtained by observation, and test after the action. The result of this study shows that the implementation of learning model Talking Stick and Course Review Horey on economics subject can increase students activeness and learning outcomes in class grade X-2 MA Miftahul Falah Pasuruan. Students activeness at the cycle I obtained 58% while at cycle II students activeness increases to be 83%. Learning outcomes at the cycle I obtained 62% while at the cycle II learning outcomes increases to be 100%.Â Keywords: Talking Stick, Course Review Horey, Learning Outcome